Computational Investigation of the Adsorption of Polyalkylene Glycols on Copper Surfaces for Copper Electrodeposition. Issue 1 (21st November 2019) - Schmidt, Ralf; Knaup, Jan Michael; von Horsten, Hermann Frank
Abstract: Adsorption of polyalkylene glycols such as polyethylene glycol (PEG) and polypropylene glycol (PPG) at the copper–water interface are studied in terms of simulations. The results are compared to spectroscopic data from available literature and reveal different contributions to the binding mode at the interface. The alignment of the polymers is determined by the interactions to both chloride‐covered copper surfaces and water. Adsorption is accompanied by conformational changes along the backbones of the molecules, which allow the observed alignment. Free energy surfaces of polymer fractions with copper ions reveal the formation of complexes with cuprous ions and support literature‐known experimental data that suggests contribution of such complexes to the adsorption. The detailed understanding of the binding mechanism of polyalkylene glycols to copper surfaces that results from this work is of crucial importance for the development of novel organic additives for electrolytic copper deposition, especially for demanding semiconductor applications. Abstract : The adsorption of polyalkylene glycols at the copper–water interface is studied in terms of molecular dynamics simulations. Comparison of the results to spectroscopic data reveal a detailed mechanistic understanding of the adsorption mechanism. These results are of crucial importance for the development of novel organic additives for industrially relevant electrolytic copper deposition.